Apakah Risiko Perusahaan dapat Memediasi Hubungan antara Pengungkapan CSR dan Asimetri Informasi? Studi Empiris di Indonesia - Irdha Yusra; Syukri Lukman; Rida Rahim; Fajri Adrianto (Jurnal Ecogen, 2025)
This study examines the effect of corporate social responsibility (CSR) disclosure on information asymmetry in the Indonesian capital market, with firm risk as a mediating variable in a green finance setting. CSR disclosure is viewed as a strategic transparency instrument that can reduce uncertainty about firms’ environmental, social, and governance practices and, therefore, lower information asymmetry between managers and outside investors. Using a sample of listed firms in Indonesia, CSR disclosure is measured through a content analysis–based index, while information asymmetry is proxied by relative bid–ask spread. Firm risk is captured by stock return volatility.  The empirical model uses regression and mediation analysis, with the help of the Smart PLS program. Based on the analysis results, it was found that CSR disclosure was proven to play a significant role in reducing information asymmetry in the Indonesian capital market, thus confirming the relevance of CSR disclosure as a mechanism for transparency and strengthening the quality of the information environment within the framework of green finance. However, CSR disclosure does not have a significant effect on corporate risk, and corporate risk also does not have a significant effect on information asymmetry, so empirically, the risk variable is unable to mediate the relationship between CSR disclosure and information asymmetry.